Tingkat Toleransi Tanaman Lamtoro mini (Desmanthus virgatus) terhadap Cekaman Salinitas melalui Teknik Kultur Jaringan: Tolerance Level of Desmanthus virgatus to Salinity Stress through Tissue Culture Techniques (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2022)
Desmanthus virgatus has high potential as a source of animal feed and has the  opportunity to develop as forage crops in saline areas. This study  aimed to obtain information on the tolerance level of D.virgatus to salinity stress at different levels using tissue culture techniques. The experimental design  used was a completely randomized design (CRD) with 5 treatments and 25 replications. The treatments were P0 (NaCl 0 ppm), P1 (NaCl 2500 ppm), P2 (NaCl 5000 ppm), P3 (NaCl 7500 ppm), and P4 (NaCl 10000 ppm). The variables observed were plant height, number of compound leaves, number of leaf twigs, leaf color, leaf loss, and plant viability. The results showed that the addition of NaCl with a level of more than 2500 ppm had a significant (p